IMPACT OF MENOPAUSAL HORMONE THERAPY AND PHYSICAL ACTIVITY ON THE INCIDENCE OF DEPRESSION IN WOMEN DURING MENOPAUSAL TRANSITION - Putri, Nadia Rahma (Journal of Psychiatry Psychology and Behavioral Research, 2025)
Introduction – Menopausal women will experience symptoms as a result of changes that occur in their bodies, both due to aging and hormonal changes. Changes in estrogen levels during menopause are associated with a wide variety of problems that arise both physically and psychologically. These problems, if not appropriately addressed, will cause a decrease in quality of life that can encourage menopausal women to experience depression. The use of hormone therapy is reported to be effective for reducing menopausal symptoms. In addition to providing therapy, doing physical activity is beneficial for reducing symptoms of depression during the menopausal transition. This paper aims to discuss the impact of women's use of hormone therapy and physical activity during the menopausal transition on the incidence of depression. Methods – This article uses the literature review method. The article used is an original research article in English and was published within the last 5 years (2019-2023). The electronic databases used are Google Scholar, Pubmed, BMC Journal, and Sciencedirect. Results – Hormone therapy given during the menopausal transition can increase the risk of depression. The amount of hormone therapy obtained does not affect the incidence of depression; the use of estrogen hormone therapy and its combination of>1 year and hormone therapy given systemically will increase the incidence. Discuss – Postmenopausal women who use hormone therapy will be at higher risk for depression. Low physical activity will pose a higher risk for depression, especially in postmenopausal women. Conclusion – The use of hormone therapy or hormone replacement therapy during the menopausal transition period can cause an increase in depression and depressive symptoms. Physical activity can help reduce symptoms of depression. In addition, physical activity can also help relieve menopausal symptoms that occur during the transition period.